An AIE fluorescent sensor for rapid and selective detection of phosgene. Issue 34 (11th April 2022) - Da-xue, Li; Dan, Li; Liang, Zong; Yan-hua, Xiao; Shao-hui, Sui; Bo, Zhuang; Rui, Li; Hong-ling, Zhen; Jian, Li; Zhi-ping, Huang; Zhi-gang, Jiang; Wei-hui, Wu
Abstract : Herein, a sensor of TPE-phos has been rationally designed for phosgene detection via formation of TPE-CN and an AIE fluorescence 'light-up'. Abstract : Herein, an aggregation-induced emission (AIE)-based sensor, 4-(1, 2, 2-triphenylvinyl)benzoxime (TPE-phos), has been rationally designed for phosgene detection. The sensor has a tetraphenylethylene unit combined with an oxime moiety. TPE-phos undergoes nitrile formation after the oxime group reacts with phosgene, which will give a significant "light-up" fluorescence due to the AIE effect within seconds.